1998
DOI: 10.1016/s0014-5793(98)01174-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired production of nitric oxide, superoxide, and hydrogen peroxide in glucose 6‐phosphate‐dehydrogenase‐deficient granulocytes

Abstract: Since the generation of superoxide and hydrogen peroxide by NADPH oxidase and nitric oxide (NO) by NO synthase (NOS) in granulocytes is NADPH-dependent, we investigated the production of NO, superoxide and H P O P in glucose 6-phosphate dehydrogenase (G6PD)-deficient human granulocytes. Our results showed that upon stimulation with either 5 W Wg/ml of lipopolysaccharide (LPS) or 10 W WM of phorbol 12-myristate 13-acetate (PMA), the production of nitrite in normal granulocytes was elevated, 252 þ 135% and 239 þ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…The involvement of G6PD in iNOS gene expression was supported further by the inhibition of NO production and iNOS protein expression by the treatment with the antisense DNA oligomer of G6PD mRNA. Although these results indicated the involvement of PPP in glucose-mediated upregulation of LPS-induced expression of iNOS, several previous studies have suggested that the inhibition or deletion of G6PD decreases the LPS-induced NO production without altering the iNOS protein levels (Laychock and Bauer, 1996;Tsai et al, 1998). Because NADPH plays a role, as a cofactor, in the synthesis of NO, NO production is reduced by NADPH depletion evoked by PPP inhibition at an enzymatic level.…”
Section: Discussionmentioning
confidence: 68%
“…The involvement of G6PD in iNOS gene expression was supported further by the inhibition of NO production and iNOS protein expression by the treatment with the antisense DNA oligomer of G6PD mRNA. Although these results indicated the involvement of PPP in glucose-mediated upregulation of LPS-induced expression of iNOS, several previous studies have suggested that the inhibition or deletion of G6PD decreases the LPS-induced NO production without altering the iNOS protein levels (Laychock and Bauer, 1996;Tsai et al, 1998). Because NADPH plays a role, as a cofactor, in the synthesis of NO, NO production is reduced by NADPH depletion evoked by PPP inhibition at an enzymatic level.…”
Section: Discussionmentioning
confidence: 68%
“…For example, it has been demonstrated that activation or overexpression of G6PD increases NO production in RINm5F rat insulinoma cells and bovine aortic endothelial cells (38,39). Also, it has been reported that inhibition of G6PD decreases ROS and RNS in various cell types, including macrophages (40), granulocytes (20), and bovine colonary arteries (41). Therefore, it is very likely that the physiological roles of G6PD might be dependent on cell types that have distinct microenvironments, with different levels of pro-oxidative and antioxidative enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrite was measured using the Griess reaction (20). Culture media (100 l) were collected and incubated with an equal volume of Griess reagent for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of cellular nitrite, hydrogen peroxide, and ROS levels. Nitrite was measured using the Griess reaction (25). Culture media (100 l each) were collected and incubated with an equal volume of Griess reagent for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%